Comprensión lectora en estudiantes de sexto de primaria y nivel de instrucción de las madres de IIEE de Ventanilla - Marcelo Risco, Petronila (2010)
The study aimed to determine whether there is an association in the levels of reading comprehension and the educational level of mothers. The descriptive design used was correlational, non-probabilistic, the sample consisted of 114 students of sixth grade primary of a low socioeconomic stratum from educational institutions outside Ventanilla. The instrument used was the test for evaluation of the reading comprehension ACL 6º (Catalá G., Catalá M., Molina E. y Monclús R., 2001) adapted by Ortega and Ramirez (2009). The results showed that the association between the level of reading comprehension reorganization and the level of education of the mother Chi Square = 0.015 is less than p_valor = 0.05.